Subthalamic nucleus deep brain stimulation is neuroprotective in the A53T α‐synuclein Parkinson's disease rat model. Issue 6 (9th June 2017) - Musacchio, Thomas; Rebenstorff, Maike; Fluri, Felix; Brotchie, Jonathan M.; Volkmann, Jens; Koprich, James B.; Ip, Chi Wang
Abstract : Objective: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is a highly effective symptomatic therapy for motor deficits in Parkinson's disease (PD). An additional, disease‐modifying effect has been suspected from studies in toxin‐based PD animal models, but these models do not reflect the molecular pathology and progressive nature of PD that would be required to evaluate a disease‐modifying action. Defining a disease‐modifying effect could radically change the way in which DBS is used in PD. Methods: We applied STN‐DBS in an adeno‐associated virus (AAV) 1/2‐driven human mutated A53T α‐synuclein (aSyn)‐overexpressing PD rat model (AAV1/2‐A53T‐aSyn). Rats were injected unilaterally, in the substantia nigra (SN), with AAV1/2‐A53T‐aSyn or control vector. Three weeks later, after behavioral and nigrostriatal dopaminergic deficits had developed, rats underwent STN‐DBS electrode implantation ipsilateral to the vector‐injected SN. Stimulation lasted for 3 weeks. Control groups remained OFF stimulation. Animals were sacrificed at 6 weeks. Results: Motor performance in the single pellet reaching task was impaired in the AAV1/2‐A53T‐aSyn–injected stim‐OFF group, 6 weeks after AAV1/2‐A53T‐aSyn injection, compared to preoperative levels (–82%; p < 0.01). Deficits were reversed in AAV1/2‐A53T‐aSyn, stim‐ON rats after 3 weeks of active stimulation, compared to the AAV1/2‐A53T‐aSyn stim‐OFF rats (an increase of ∼400%; p < 0.05), demonstrating a beneficial effect of DBS. This motor improvement was maintained when the stimulation was turned off and was accompanied by a higher number of tyrosine hydroxylase + SN neurons (increase of ∼29%), compared to AAV1/2‐A53T‐aSyn stim‐OFF rats ( p < 0.05). Interpretation: Our data support the putative neuroprotective and disease‐modifying effect of STN‐DBS in a mechanistically relevant model of PD. Ann Neurol 2017;81:825–836